Identification, structure modification, and characterization of potential small-molecule SGK3 inhibitors with novel scaffolds. (December 2018) - Gong, Grace; Wang, Ke; Dai, Xin-Chuan; Zhou, Yan; Basnet, Rajesh; Chen, Yi; Yang, De-Hua; Lee, Woo-Jeong; Buchanan, Christina; Flanagan, Jack; Shepherd, Peter; Chen, Ying; et al.
Abstract The serum and glucocorticoid-regulated kinase (SGK) family has been implicated in the regulation of many cellular processes downstream of the PI3K pathway. It plays a crucial role in PI3K-mediated tumorigenesis, making it a potential therapeutic target for cancer. SGK family consists of three isoforms (SGK1, SGK2, and SGK3), which have high sequence homology in the kinase domain and similar substrate specificity with the AKT family. In order to identify novel compounds capable of inhibiting SGK3 activity, a high-throughput screening campaign against 50, 400 small molecules was conducted using a fluorescence-based kinase assay that has a Z' factor above 0.5. It identified 15 hits (including nitrogen-containing aromatic, flavone, hydrazone, and naphthalene derivatives) with IC50 values in the low micromolar to sub-micromolar range. Four compounds with a similar scaffold (i.e., a hydrazone core) were selected for structural modification and 18 derivatives were synthesized. Molecular modeling was then used to investigate the structure-activity relationship (SAR) and potential protein–ligand interactions. As a result, a series of SGK inhibitors that are active against both SGK1 and SGK3 were developed and important functional groups that control their inhibitory activity identified.